Diversitas Tenaga Kerja: Tantangan dan Strategi Pengelolaannya - Diah Kusumardhani S. (Sinergi: Kajian Bisnis dan Manajemen, 2005)
Diversity has become one of the most often used words of our time-and a word almost never defined. The labor force is becoming more diverse in terms of ethnicity, race, sex, sexual orientation, disability, and other cultural factors. To succeed as a manager in the twenty-first century, you must work effectively with people who are different from you. Mana¬ging workforce diversity in a way that both respects the employee and promotes a shared sense of corporate identity and vision is one of the greatest challenges facing organizations today. Recognizing the importance of leadership diversity is only the first step. No change will occur unless an effective strategy is developed for achieving inclusion through a commitment to diversity at all levels of the workforce, especially at the senior management level, where it is most strategically important and least in evidence. This paper discuss about what diversity is, why we have to manage it, what its challenges are, and what strategies that future mana¬gers can adopt in order to take advantage of the benefits of diversity while avoiding its pitfalls.Keywords:     work force diversity, managerial challenge, managing diversity, and effective strategy.